Bedazzle: Photographing Western Australia’s Gold Towns - Costantino, Thea (FORM, 2016)
The former Gold Rush sites visited as part of the Bedazzle development residencies are layered with personal, family and cultural narratives. The works made for this exhibition respond to the experience of retracing and return, and culminates in a set of anxious, dream-like narratives referencing failed rites of identity formation, migration and domesticity. The photographs Bride, Cabbage wife and Home coming are staged portraits depicting women at moments of transition. Masks and other indicators of disassociated states have played a prominent role in my practice for a number of years now, reflecting my ongoing investigation of the grotesque as a means to envisage an uncanny relationship with the past. The digital collages of the Città fantasma series respond to the abandoned Gwalia town site, a predominantly Italian mining settlement set up by Herbert Hoover. The images reference the role of Italian labour in WA history and Australia’s complex relationship with migration, but also construct an impression of disconnection and dislocation that relates to the inherited legacies of migration for subsequent generations. The sculptures of the Daughters of Midas series are fantastical responses to the mythologized history of European women in the Goldfields, narratives that tend to uncritically celebrate the role of women in the colonial project. After showing at FORM Gallery in Perth, this exhibition has toured to the Courthouse Gallery in Port Headland and the Goldfields Arts Centre in Kalgoorlie. It received positive critique in local media.